Do Humans Translate like Machines? Students’ Conceptualisations of Human and Machine Translation - Salmi Leena; Dorst Aletta G.; Koponen Maarit; Zeven Katinka (Finland, 2025)
This paper explores how students conceptualise the processes involved in human and machine translation, and how they describe the similarities and differences between them. The paper presents the results of a survey involving university students (B.A. and M.A.) taking a course on translation who filled out an online questionnaire distributed in Finnish, Dutch and English. Our study finds that students often describe both human translation and machine translation in similar terms, suggesting they do not sufficiently distinguish between them and do not fully understand how machine translation works. The current study suggests that training in Machine Translation Literacy may need to focus more on the conceptualisations involved and how conceptual and vernacular misconceptions may affect how translators understand human and machine translation.
Proceedings of the 24th Annual Conference of the European Association for Machine Translation